Research on the Turkic Peoples - Baurzhan Yerdembekov, Alya Oskembay, Bakytzhan Kelgembaeva, (Opción, 2019)
The article analyzes the work of the famous Russian scientist-orientalist of the late XIX – the first half of XX centuries, who was working in the field of Turkic studies via study of contextual features related to identity structure in the works of other authors. As a result, the Barthold was the one to make a significant contribution to the Turkic studies development. Analysis of V.V. Bartold’s works on the Turkic peoples of the Central Asia allows concluding that Barthold has formed the basis for a deeper understanding of their culture, way of life and traditions